On music theory and making music more welcoming for everyone. - Ewell, Philip (Music and social justice., 2023)
"Since its inception in the mid-twentieth century, American music theory has been framed and taught almost exclusively by white men. As a result, whiteness and maleness are woven into the fabric of the field, and BIPOC music theorists face enormous hurdles due to their racial identities. In On Music Theory, Philip Ewell brings together autobiography, music theory and history, and theory and history of race in the United States to offer a black perspective on the state of music theory and to confront the field's white supremacist roots. Over the course of the book, Ewell undertakes a textbook analysis to unpack the mythologies of whiteness and western-ness with respect to music theory, and gives, for the first time, his perspective on the controversy surrounding the publication of volume 12 of the Journal of Schenkerian Studies. He speaks directly about the antiblackness of music theory and the antisemitism of classical music writ large and concludes by offering suggestions about how we move forward. Taking an explicitly antiracist approach to music theory, with this book Ewell begins to create a space in which those who have been marginalized in music theory can thrive" --